Hubungan penanganan atonia uteri terhadap tindakan KBI dan KBE - Rizki, Hudeni; Sihaloho, Endang; Sinulingga, Yeni Friska; Daulay, Evlindari Sentani; Ristiani, Ristiani (JOURNAL OF Qualitative Health Research & Case Studies Reports, 2026)
Background: Uterine atony is a major cause of postpartum hemorrhage, contributing significantly to maternal morbidity and mortality. Prompt and appropriate management of uterine atony, including the use of manual interventions such as Internal Bimanual Compression (IBC) and External Bimanual Compression (EBCC), is crucial for successful hemorrhage control and the prevention of further complications. However, clinical practice still finds variation in the quality of uterine atony management and the implementation of IBC and ECCC procedures. Purpose: To determine the relationship between uterine atony management and IBC and ECCC procedures. Method: This was an observational analytical study using a cross-sectional approach conducted at the Helen Tarigan Clinic, with data collected from July to November 2025. A sample of 34 women giving birth with uterine atony was selected using a total sampling technique. Data were obtained through a review of medical records and analyzed univariately and bivariately using the Chi-Square test with a significance level of α = 0.05. Results: There was a significant association between uterine atony management and IBC and IBC procedures, with a p-value of 0.032. Good uterine atony management was more frequently followed by IBC and IBC procedures than suboptimal management. Conclusion: Uterine atony management was significantly associated with IBC and IBC procedures, thus optimizing initial management plays a crucial role in controlling postpartum hemorrhage.   Keywords: Bimanual Compression; Postpartum Hemorrhage; Uterine Atony.   Pendahuluan: Atonia uteri merupakan penyebab utama perdarahan postpartum yang berkontribusi signifikan terhadap morbiditas dan mortalitas maternal. Penanganan atonia uteri yang cepat dan tepat, termasuk penggunaan intervensi manual seperti Kompresi Bimanual Internal (KBI) dan Kompresi Bimanual Eksternal (KBE), sangat menentukan keberhasilan pengendalian perdarahan serta pencegahan komplikasi lanjutan. Namun, dalam praktik klinis masih ditemukan variasi dalam kualitas penanganan atonia uteri dan penerapan tindakan KBI serta KBE. Tujuan: Untuk mengetahui hubungan antara penanganan atonia uteri terhadap tindakan KBI dan KBE. Metode: Penelitian analitik observasional dengan pendekatan cross-sectional yang dilaksanakan di Klinik Helen Tarigan dengan pengumpulan data pada periode Juli hingga November 2025. Sampel berjumlah 34 ibu bersalin dengan atonia uteri yang dipilih menggunakan teknik total sampling. Data diperoleh melalui telaah rekam medis dan dianalisis secara univariat dan bivariat menggunakan uji Chi-Square dengan tingkat kemaknaan α = 0.05. Hasil: Terdapat hubungan yang bermakna antara penanganan atonia uteri dengan tindakan KBI dan KBE, dengan nilai p-value sebesar 0.032. Penanganan atonia uteri yang baik lebih banyak diikuti dengan pelaksanaan tindakan KBI dan KBE dibandingkan penanganan yang kurang optimal. Simpulan: Penanganan atonia uteri berhubungan secara signifikan dengan tindakan KBI dan KBE, sehingga optimalisasi penanganan awal berperan penting dalam pengendalian perdarahan postpartum.   Kata Kunci: Atonia Uteri; Kompresi Bimanual; Perdarahan Postpartum.